The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/eye.2017.117
|View full text |Cite
|
Sign up to set email alerts
|

Topical administration of Esculetin as a potential therapy for experimental dry eye syndrome

Abstract: PurposeIn this study, we investigated the therapeutic effects of topical Esculetin for dry eye rabbits through the ocular tests, inflammatory factor levels and specific phosphorylated protein expressions of ERK1/2 singnal pathway.Patients and methodsThirty-two healthy adult male New Zealand white rabbits were chosen for the study. DES models were established after removing of the main lacrimal gland, Harderian gland and nictitating membrane in the left eyes and randomly divided into group DES control, group Cs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Therefore, evaluation of inflammatory cytokines in the ocular surface epithelial (epithelium of cornea or conjunctiva) cells, such as IL-1β, IL-8, TNF-α, and matrix metalloproteinases (MMPs), is the most common feature in experimental models [81,84,[138][139][140]. Alongside the underlying stimulating factors of inflammation in the ocular surface, such as MAP kinase pathways (ERK, JNK, and P38) [140,148], NFkB has also been measured by many researchers. Since ocular surface stress and inflammation induce apoptosis, apoptosis-related factors BAX, BCl2, and their ratio were also measured [88].…”
Section: Analysis Of Molecular Changes and Histopathological Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, evaluation of inflammatory cytokines in the ocular surface epithelial (epithelium of cornea or conjunctiva) cells, such as IL-1β, IL-8, TNF-α, and matrix metalloproteinases (MMPs), is the most common feature in experimental models [81,84,[138][139][140]. Alongside the underlying stimulating factors of inflammation in the ocular surface, such as MAP kinase pathways (ERK, JNK, and P38) [140,148], NFkB has also been measured by many researchers. Since ocular surface stress and inflammation induce apoptosis, apoptosis-related factors BAX, BCl2, and their ratio were also measured [88].…”
Section: Analysis Of Molecular Changes and Histopathological Changesmentioning
confidence: 99%
“…In DED, goblet cells were also reduced, which is responsible for mucin secretion. Conjunctival impression cytology (CIC) using hematoxylin and periodic acid-Schiff (PAS) reagent [79,148] or counting goblet cells in the conjunctiva using periodic acid-Schiff (PAS) staining [44,84]. Immunohistochemical slides were also stained with MUC5AC in the conjunctiva to count the goblet cells [79,83,138].…”
Section: Analysis Of Molecular Changes and Histopathological Changesmentioning
confidence: 99%
“…The inhibition of phosphorylation of the p38 downstream substrate MAPKAPK2 reduced inflammation and ocular surface damage in a DED mouse model [160]. In a rabbit DED model, the Chinese plant, Esculetin, reduced inflammation and dry eye symptoms through specific inhibition of the ERK1/2 pathway [161], and recently it has been reported that an oral administration of Dendrobium officinale extract downregulated the phosphorylation of ERK in human corneal keratocytes and upregulated various aquaporins, while its oral administration in rats enhanced tear production and had a protective effect on ocular surface damage [162]. Accordingly, the levels of the three MAPK signaling pathways and inflammation were rapidly increased in a mouse DED model and remain elevated after 5 days [158].…”
Section: Mapk In the Corneamentioning
confidence: 99%
“…For example, esculetin (20-60 mg/kg) can inhibit the production of inflammatory factors such as IL-1β, IL-6, TNF-α, C-C motif chemokine ligand 2 and iNOS in Escherichia coli-induced sepsis mice by inhibiting the NF-κB and STAT1/STAT3 signaling pathways (95). In a rabbit model in which the primary lacrimal gland, sclerotial gland, and cornea were removed to induce dry eye, esculetin (0.05% of the diet) was able to inhibit the expression of IL-1α, IL-1β, and TNF-α by inhibiting the ERK1/2 signaling pathway and thereby suppressing IL-1α, IL-1β, and TNF-α (96). Furthermore, esculetin (10-20 mg/kg) inhibits the expression of TNF-α and IL-6 in isoproterenol induced myocardial toxicity in rats by inhibiting the activation of the NF-κB signaling pathway (97).…”
Section: Lung Inflammationmentioning
confidence: 99%